Intravitreal ranibizumab injection in the treatment of refractory diabetic macular edema - Kobat, Sabiha Güngör; Turgut, Burak; Çeliker, Ülkü; Demir, Tamer (Gazi Eye Foundation, 2014)
Purpose: To evaluate the efficacy of intravitreal ranibizumab injection in the treatment of refractory diabetic macular edema (DME). Matterials and Methods: 58 eyes of 43 patients with refractory DME were enrolled into the study. The mean age of the patients were 61.60±8.72 years. Patients were applied 3 doses of 0.5 mg intravitreal ranibizumab injection with interval period of one month. Best corrected visual acuities (BCVA) and optical coherence tomography (OCT) images of patients before and after injection were recorded. Results: The mean duration was 8.4 months. Mean BCVAs before and after the treatment were 0.87±0.40 logMAR, and 0.84±0.42 logMAR, respectively. The change at BCVA between before and after the treatment was not significant (p>0.05). At the first month after 3 doses of injection the visual acuity of 11 eyes (18.96%) were increased 1 line (5 letters) and more. There was not any significant increase in visual acuity in 41 eyes (70.70%) The visual acuity decreased in six eyes (10.34%). The mean central macular thickness (CMT) before and after injections were calculated as 528.27±111.31 and 450.34±128.29 ?m, respectively. The mean reduction amount in CMT was 77.93±127.11 ?m and it was significant (p<0.001). After 3 doses of injection, OCT showed that the macular edema in 38 eyes (65.52%) were reduced compare to before the injection. There was no changing in 10 eyes (17.24%. Macular edema was increased in 10 eyes (17.24%). Conclusion: It was observed that ranubizumab injections anatomically improved macular edema but not visual acuity. This discrepancy might be related to foveal photoreceptor damage or poor regulation of blood sugar level.
Keywords: Diabetes; Ranibizumab; Refractory macular edema